IJCM_12A: Parental perception on surgical care in public and private health care systems - Krupa T V Sai; Baliga Kiran N; Baliga B S; Nayak Anupama P; Reddy Bharath (Wolters Kluwer Medknow Publications, 2024)
Background: The purpose of the study is to assess the perception of parents on surgical care in public and private healthcare systems. It encompasses factors like quality of care, convenience, and expenditure that provide satisfaction, which has a crucial role in shaping parental perception. Objective: To compare the perception of parents regarding the quality of care provided to children for surgical care in public and private health care systems. Methodology: The questionnaire was constructed in three languages and distributed to 125 patients. Details regarding the levels of perception among parents and its significance in the Public and Private sectors included 6 questions - Convenience of location, Length of time spent, Equipment, comfort, explanation of the condition, and overall stay. Results: Overall satisfaction was seen to be 54.67% for the households admitted in the private healthcare sector compared to 59.27% in the public healthcare sector. Comfort was 52.53% and 66.24% in private and public health care services respectively. The personal manner of doctors was 57.87% in private and 58.72% in the public health care sector. Conclusion: Overall satisfaction level in public hospitals was better when compared with the private sector, even though, the difference between the satisfaction level for the quality of care provided in public and private in our study was not significant.